HLA genotyping in the clinical laboratory: comparison of next‐generation sequencing methods. (14th August 2016) - Profaizer, T.; Lázár‐Molnár, E.; Close, D.W.; Delgado, J. C.; Kumánovics, A.
Abstract: Implementation of human leukocyte antigen (HLA) genotyping by next‐generation sequencing (NGS) in the clinical lab brings new challenges to the laboratories performing this testing. With the advent of commercially available HLA‐NGS typing kits, labs must make numerous decisions concerning capital equipment and address labor considerations. Therefore, careful and unbiased evaluation of available methods is imperative. In this report, we compared our in‐house developed HLA NGS typing with two commercially available kits from Illumina and Omixon using 10 International Histocompatibility Working Group (IHWG) and 36 clinical samples. Although all three methods employ long range polymerase chain reaction (PCR) and have been developed on the Illumina MiSeq platform, the methodologies for library preparation show significant variations. There was 100% typing concordance between all three methods at the first field when a HLA type could be assigned. Overall, HLA typing by NGS using in‐house or commercially available methods is now feasible in clinical laboratories. However, technical variables such as hands‐on time and indexing strategies are sufficiently different among these approaches to impact the workflow of the clinical laboratory.